The Connotation, Characteristics, Composition and Significance of Subject Matter Knowledge (SMK) of Mathematics Teachers in China. - Li, Baozhen (African & Asian Studies, 2021)
The connotation of SMK of mathematics teachers is the intelligent result of dynamic construction about different types of mathematical knowledge in the process of their learning, teaching and research. The SMK of mathematics teachers is characterized by the individuality of cognitive construction of teachers, generation of the interaction among learning, teaching and research, continuity of teachers' integrative pre-service and in-service education, mutual activation of subjective teaching knowledge, interwovenness with students' learning and so on. The SMK of mathematics teachers is composed of 4 parts, including knowledge of mathematical content, knowledge of mathematical history and mathematical culture, knowledge of mathematical thoughts and methods, and view of mathematics. And these four components correlate with each other and they are inseparable. Interpreting and revealing the connotation, characteristics and composition of subject knowledge of mathematics teachers are of theoretical significance to the improvement of mathematics teachers' personal knowledge structure, the adjustment of curriculum, and the determination of the training program content for in-service mathematics teachers as well as the orientation of mathematics teachers' recruitment and the offering of reference for the national education administration in formulating relevant policies on teachers' professional development.